Three Cycles : Housing, Credit, and Real Activity - Tamirisa, Natalia (IMF Working Papers; Working Paper ;, 2009)
We examine the characteristics and comovement of cycles in house prices, credit, real activity and interest rates in advanced economies during the past 25 years, using a dynamic generalized factor model. House price cycles generally lead credit and business cycles over the long term, while in the short to medium term the relationship varies across countries. Interest rates tend to lag other cycles at all time horizons. While global factors are important, the U.S. business cycle, house price cycle and interest rate cycle generally lead the respective cycles in other countries over all time horizons, while the U.S. credit cycle leads mainly over the long term.